Peran CAR, FDR, dan BOPO Terhadap Stabilitas Perbankan dengan NPF Sebagai Pemoderasi pada Bank Umum Syariah 2019-2024 - Maolana, Dimas Bagus; Rosia, Rina (Jihbiz: Global Journal of Islamic Banking and Finance, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operational Efficiency Ratio (BOPO) on banking stability with Non-Performing Financing (NPF) as a moderating variable in Islamic Commercial Banks in Indonesia during the period 2019–2024. This research uses a quantitative approach with panel data regression methods based on the annual financial statements of Islamic Commercial Banks registered with the Financial Services Authority (OJK). From a population of 14 banks, 10 banks were selected as samples using purposive sampling. The analysis was conducted using multiple regression with the Moderated Regression Analysis (MRA) test. The analytical tool used was EViews 12 software. The results of the study show that CAR has a significant positive effect on bank stability. FDR has a significant positive effect on bank stability. BOPO has a significant negative effect on bank stability. NPF does not moderate the effect of CAR on bank stability. NPF moderates the effect of FDR on bank stability. NPF does not moderate the effect of BOPO on bank stability.